Examining the correlations of hotel service quality with tourists satisfaction - Norazah Mohd Suki (IDOSI Publications, 2013)
This study aims to examine the correlation of hotel service quality (i.e. assurance, reliability, responsiveness, tangibles and empathy) with tourists’ satisfaction. Results via correlation analysis, among 200 respondents who have already experienced the tourism product and services in Federal Territory of Labuan, Malaysia revealed that service quality is significantly correlated with empathy, reliability, responsiveness and tangibles. The first served as the best predictor of tourists satisfaction followed by the latter. The findings imply the need for hotel providers to strategically leverage on these factors in its pursuit of tourists satisfaction. Direction for future study of study is also mentioned.